VERBALIZING THE VISUAL IN SHAKESPEARE’S NARRATIVE POEM VENUS AND ADONIS - Stegh Camati, Anna (Revista VIS: Revista do Programa de Pós-Graduação em Artes Visuais, 2020)
The appropriation of motifs, codes and conventions from the visual arts for structural, thematic and aesthetic purposes in verbal discourses was paramount during the Renaissance and is a recurrent practice today. The present essay aims to examine Shakespeare’s creative transposition of images from painting to poetry in his narrative poem Venus and Adonis (1593), and discuss his use of mythical themes and motifs to question gender and sexual roles current in his time. The intermedial dialogues between the visible and the legible will be addressed in the light of theoretical perspectives by Claus Clüver, Liliane Louvel, Erwin Panofsky, Farah-Karim Cooper and Laura Mulvey.